2019
DOI: 10.1155/2019/1829328
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of the Effect of Fly Ash and Slag on the Properties of Cement Asphalt Mortar

Abstract: The application of cement asphalt mortar (CAM) in modern high-speed railways has been gaining attention due to its combined merits between asphalt and cement hydration product characteristics. To promote sustainable development, it is promising to utilize by-products in the making of new CAM instead of using only cement. In this research, the cement content was partly replaced by fly ash or ground-granulated blast furnace (GGBS) slag to achieve this objective. Then, laboratory experiments were conducted to det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 14 publications
0
6
0
Order By: Relevance
“…However, it was also found in some related works of literature [10,77], that fly ash decreases the viscosity of CA mortar, thereby enhancing its workability. Le et al [23] reported that substituting cement with any fly ash or ground granulated blast furnace (GGBF) slag improves the overall fresh properties of CA mortar; these materials also prolonged the demulsification process of emulsified asphalt and retarded the hardening process of CA mortar. According to their results, though the mixture with these admixtures suffered slow early strength development as compared to the control mix, a high dosage of fly ash leads to high strength development beyond 28 days.…”
Section: Use Of Additives In Ca Mortar Productionmentioning
confidence: 99%
See 3 more Smart Citations
“…However, it was also found in some related works of literature [10,77], that fly ash decreases the viscosity of CA mortar, thereby enhancing its workability. Le et al [23] reported that substituting cement with any fly ash or ground granulated blast furnace (GGBF) slag improves the overall fresh properties of CA mortar; these materials also prolonged the demulsification process of emulsified asphalt and retarded the hardening process of CA mortar. According to their results, though the mixture with these admixtures suffered slow early strength development as compared to the control mix, a high dosage of fly ash leads to high strength development beyond 28 days.…”
Section: Use Of Additives In Ca Mortar Productionmentioning
confidence: 99%
“…According to their results, though the mixture with these admixtures suffered slow early strength development as compared to the control mix, a high dosage of fly ash leads to high strength development beyond 28 days. Indeed, favorable particle size distribution, round shape, and appreciative chemical properties of fly ash provided adequate bonding with the asphalt membrane; this helps in providing uniform structure formation in the CA mortar mixture and consequently improves long-term strength development [23]. Their research proves that the utilization of appropriate fly ash in CA mortar improves its fresh and hardened properties, reduces the cost of production, and provides an environmental solution as it utilizes industrial by-products that may rather be used as landfills and eventually cause pollution.…”
Section: Use Of Additives In Ca Mortar Productionmentioning
confidence: 99%
See 2 more Smart Citations
“…Research on emulsified asphalt cement mortar mixtures mainly focuses on the mixing ratio [7,8], performance [5,[9][10][11][12][13][14], mixing time [15], strength formation mechanism [7,16,17], and so on. For pavement materials, understanding their performance is the priority.…”
Section: Introductionmentioning
confidence: 99%